Strategi Customer Relationship Management Berbasis Influencer untuk Meningkatkan Loyalitas Konsumen pada Produk Kecantikan Lokal - Maulana, Afrizal; Purnamasari, Lathiyfah Shanti; Srimukti, Adesty; Angelita, Kezia (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2023)
In the era of rapidly growing social media, the use of influencer marketing and Customer Relationship Management (CRM) has become an important strategy in the beauty product industry. Brands rely on influencers to promote their products, while CRM focuses on building and maintaining customer relationships. However, the effective combination of these two strategies in the context of beauty products still requires deeper understanding. This study aims to analyze how CRM elements are integrated into influencer marketing practices and their impact on customer loyalty in the beauty product industry. This research uses a qualitative approach by conducting content analysis on social media. The data analyzed includes influencer posts, follower comments, and interactions between brands and customers. The results of the study show that beauty product brands adopt three main strategies in integrating CRM elements into influencer marketing. First, they use influencers from abroad to create big events that attract customer attention. Second, they chose beauty vloggers who were relevant to consumers to provide comprehensive reviews about the products. And third, they appoint celebrities to attract consumer attention. Relevant and meaningful interactions mainly occur through product review videos conducted by beauty vloggers. This research provides practical guidance for beauty product brands in optimizing the use of influencer marketing and CRM elements. In addition, this research also contributes to the literature on social media marketing and customer relationship management in this digital era.